Mechanical Improvement of Graphene Oxide Film via the Synergy of Intercalating Highly Oxidized Graphene Oxide and Borate Bridging - Yiwei Quan; Peng He; Guqiao Ding (Nanomaterials)
Converting graphene oxide (GO) nanosheets into high-performance paper-like GO films has significant practical value. However, it is still challenging because the mechanical properties significantly decreased when the nanosheets are assembled into films. The simultaneous attainment of high tensile strength, high modulus, and relatively high toughness remains a formidable challenge. Here, we demonstrated an effective approach involving the incorporation of high oxidized graphene oxide (HOGO) and borate, to enhance the mechanical properties of GO films. X-ray photoelectron spectroscopy (XPS) measurements and thermogravimetric analysis-differential scanning calorimetry (TG-DSC) revealed the synergistic effects of hydrogen and covalent bonding from HOGO and borate, respectively. Additionally, wide-angle X-ray scattering (WAXS) analysis indicated a notable enhancement in the orientation of the GO in the resulting films, characterized by the Herman’s orientation factor (ƒ = 0.927), attributable to the combined action of hydrogen and covalent bonding. The borate-crosslinked GO+HOGO films exhibited exceptional mechanical properties, with an impressive strength (417.2 MPa), high modulus (43.8 GPa), and relatively high toughness (2.5 MJ m−3). This innovative assembly strategy presents a promising avenue for achieving desirable mechanical properties, thereby enhancing the potential for commercial applications.